ADAPTATION AND VALIDATION OF THE INVENTORY OF TEACHER-STUDENT RELATIONSHIPS (IT-SR) INDONESIAN VERSION - Destriday Ifriana; Aprilia Rizki Maharani; Sarah Tsabita Kaysi; Hendriati Agustiani; Surya Cahyadi (World Psychology, 2026)
Understanding teacher–student relationships is important, as these interactions contribute to students’ academic and socio-emotional development. However, validated instruments to assess these relationships in the Indonesian context remain limited. The purpose of this study was to adapt (Murray & Zvoch, 2011) the Inventory of Teacher-Student Relationship (IT-SR) into Indonesian and assess its validity and reliability among junior high school students. The adaptation process involved obtaining permission from the original developer, translation, expert review, and a readability test with 10 students. The main data were collected from 172 students at SMP Negeri 72 Bandung and analyzed using Confirmatory Factor Analysis (CFA). The results showed that the modified model demonstrated a good fit (CFI = 0.994, TLI = 0.992, RMSEA = 0.032, SRMR = 0.077). Three items were excluded due to low factor loadings, resulting in a final 14-item instrument. Reliability analysis showed a Cronbach’s alpha of 0.828. Overall, the Indonesian version of the IT-SR is valid and reliable for measuring teacher–student relationships among junior high school students in Indonesia.